Effective instructional methodologies for children with special needs in inclusive and special education settings - Taufiq, Ahmad; Arrum Wijaya; Salamah, Siti; Priyatun, Inayah; Ahmad Ubaedi Fathuddin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Educating children with special needs (CWSN) requires instructional approaches that differ significantly from conventional methods. This study aims to identify and analyze effective teaching methodologies that support the learning process of CWSN in both inclusive settings and special education schools (Sekolah Luar Biasa – SLB). A qualitative descriptive approach was employed through a literature review methodology. The findings indicate that individualized instruction, differentiated teaching strategies, and the use of multisensory media significantly enhance engagement and comprehension among CWSN. Teachers play a pivotal role in assessing learners' needs, designing individualized education plans (IEPs), and fostering collaborative communication with parents and other support personnel. These findings underscore the importance of professional development and adaptive education policies in ensuring the educational rights of children with special needs are fully realized. The study’s implications contribute to strengthening inclusive education practices that are responsive to learner diversity.